2011
DOI: 10.1029/2009wr008540
|View full text |Cite
|
Sign up to set email alerts
|

A differential equation for specific catchment area

Abstract: Analysis of the behavior of specific catchment area in a stream tube leads to a simple nonlinear differential equation describing the rate of change of specific catchment area along a flow path. The differential equation can be integrated numerically along a flow path to calculate specific catchment area at any point on a digital elevation model without requiring the usual estimates of catchment area and width. The method is more computationally intensive than most grid‐based methods for calculating specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
94
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(100 citation statements)
references
References 45 publications
3
94
0
3
Order By: Relevance
“…where α s = specific contributing area, and tan β = local slope (Frankenberger et al, 1999;Sorenson et al, 2005). Here, specific contributing area is defined as the total upslope area contributing flow to a given location, divided by the specific contour length (Chirico et al, 2005;Galant and Hutchinson, 2011). The DEM cell edge length has been applied as the value for specific contour length in several terrain analyses (Zhang and Montgomery, 1994;Wolock and McCabe, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…where α s = specific contributing area, and tan β = local slope (Frankenberger et al, 1999;Sorenson et al, 2005). Here, specific contributing area is defined as the total upslope area contributing flow to a given location, divided by the specific contour length (Chirico et al, 2005;Galant and Hutchinson, 2011). The DEM cell edge length has been applied as the value for specific contour length in several terrain analyses (Zhang and Montgomery, 1994;Wolock and McCabe, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, if the flow is also affected by surface forces implying for instance significant pressure or stress gradients, then flow lines are not necessarily the same as slope lines and flow dispersion becomes a relevant process. The distinction between slope and flow lines is outlined by Tarboton [1997] and Orlandini et al [2003], and is explicitly made by Gallant and Hutchinson [2011]. In light of this distinction, the term “flow direction method” used in terrain analysis, hydrology, and fluvial geomorphology may not be entirely appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The attention is focused in this paper on dominant classes of terrain analysis methods designed to process grid digital elevation models. Reviews of these methods can be found by Tarboton [1997], Orlandini and Moretti [2009], and Gallant and Hutchinson [2011]. Methods designed to process contour digital elevation models [e.g., Moretti and Orlandini , 2008] or based on the aspect driven method of Lea [1992] [e.g., Costa‐Cabral and Burges , 1994] are not evaluated in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…extraction because they are able to simulate stream flow over the terrain (Freeman, 1991;Gallant & Hutchinson, 2011;Holmgren, 1994;Ibbitt, Willgoose, & Duncan, 1999;O'Callaghan & Mark, 1984;Orlandini, Moretti, Franchini, Aldighieri, & Testa, 2003;Pilesjö & Hasan, 2014;Quinn, Beven, Chevallier, & Planchon, 1991;Tarboton, 1997;Turcotte, Fortin, Rousseau, Massicotte, & Villeneuve, 2001;Xiong, Tang, Yan, Zhu, & Sun, 2014;Zhou, Pilesjö, & Chen, 2011).…”
mentioning
confidence: 99%